2018
DOI: 10.1152/japplphysiol.00689.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in iPSC-derived neurons of subjects with chronic mountain sickness

Abstract: Patients with chronic mountain sickness (CMS) suffer from hypoxemia, erythrocytosis, and numerous neurologic deficits. Here we used induced pluripotent stem cell (iPSC)-derived neurons from both CMS and non-CMS subjects to study CMS neuropathology. Using transmission electron microscopy, we report that CMS neurons have a decreased mitochondrial volume density, length, and less cristae membrane surface area. Real-time PCR confirmed a decreased mitochondrial fusion gene optic atrophy 1 (OPA1) expression. Immunob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Whereas normoxia-induced gene expression changes were previously found in Andeans, those changes were absent in Ethiopians, as they are in Himalayans. This is consistent with physiologic studies finding no increase in cerebral circulation and hypoxic ventilatory drive in Ethiopians and Himalayans at high altitude, and with the absence of chronic mountain sickness on the East African altitude plateau [ 5 ], as in Tibet—and in contrast to the Andes [ 11 , 12 ].…”
Section: Simien Mountains Ethiopiasupporting
confidence: 90%
See 1 more Smart Citation
“…Whereas normoxia-induced gene expression changes were previously found in Andeans, those changes were absent in Ethiopians, as they are in Himalayans. This is consistent with physiologic studies finding no increase in cerebral circulation and hypoxic ventilatory drive in Ethiopians and Himalayans at high altitude, and with the absence of chronic mountain sickness on the East African altitude plateau [ 5 ], as in Tibet—and in contrast to the Andes [ 11 , 12 ].…”
Section: Simien Mountains Ethiopiasupporting
confidence: 90%
“…We found evidence of altered mitochondrial morphology and function in the cultured neurons of subjects with chronic mountain sickness. We also saw increased cell death under the hypoxia prevailing in Cerro de Pasco due, in part, to altered mitochondrial dynamics [ 6 , 8 , 12 ].…”
Section: Cerro De Pasco Perumentioning
confidence: 99%
“…We have previously reported that CMS neurons had altered mitochondrial dynamics and function ( Zhao et al, 2018 ). Due to the fact that ER and mitochondria form physical contact through MAM and interact with each other functionally ( Bouman et al, 2011 ; Senft and Ronai, 2015 ), we examined whether the altered mitochondrial function activates the ER stress response.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to sample availability and ethical issues, our understanding of CMS neuropathology in humans remains largely unexplored at cellular and molecular levels. By using CMS disease-specific iPSC-derived neurons, we have previously reported mitochondrial dysfunction in CMS neurons under normoxia and an increased vulnerability to hypoxia-induced cell death after 48 h ( Zhao et al, 2018 ). Here, we are interested in investigating the underlying mechanisms that contribute to hypoxia-induced cell death in CMS neurons.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, LS and Leigh-like syndrome have been linked to pathogenic mutations in genes encoding proteins regulating crista architecture, including SLC25A46 ( Janer et al., 2016 ) and OPA1 ( Finsterer and Zarrouk-Mahjoub, 2017 ). Indeed, LS-causing mutations in SLC25A46 result in abnormal mitochondrial architecture, including significantly shortened cristae ( Janer et al., 2016 ), whereas disease mutations that reduce OPA1 expression produce decreased mitochondrial volume density and diminished cristae membrane surface area ( Zhao et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%